2018
DOI: 10.15406/mojfpt.2018.06.00183
|View full text |Cite
|
Sign up to set email alerts
|

Medicinal uses and health benefits of chili pepper (Capsicum spp.): a review

Abstract: Pepper have been grown and used in Eritrea for long period of time and is part of the Eritrean food culture. Eritrean pepper germplasm was found to be highly diversified that can serve different uses and purposes. Globally pepper is known for its high nutritional value, health benefits and medicinal properties. It is reach (Rich) in vitamins and minerals, has antimicrobial and anticancer properties. Chili pepper has preventive and therapeutic properties for many ailments such as different types of cancer, rheu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(77 citation statements)
references
References 0 publications
0
75
0
2
Order By: Relevance
“…In accordance with the World Health Organization, inquiries about its toxicity, safety, potency, value, accessibility, protection, and additional improvement are required. It was revealed that about 4 out of 10 people in the UK employ alternative medicine sometimes in their lives [14]. Therefore, the aim of this work is to focus on the nutritional value, morphology and extraction procedures as well as the therapeutic properties and uses, recommended doses, toxicity, and pharmacokinetics of chili pepper.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with the World Health Organization, inquiries about its toxicity, safety, potency, value, accessibility, protection, and additional improvement are required. It was revealed that about 4 out of 10 people in the UK employ alternative medicine sometimes in their lives [14]. Therefore, the aim of this work is to focus on the nutritional value, morphology and extraction procedures as well as the therapeutic properties and uses, recommended doses, toxicity, and pharmacokinetics of chili pepper.…”
Section: Introductionmentioning
confidence: 99%
“…High enzyme amount is obtained from Capsicum annuum, which belong to familySolanaceae.Globally pepper is known for its high nutritional value, health benefits and medicinal properties. It is rich in vitamins and minerals, has antimicrobial and anticancer properties (Saleh et al, 2018). The specific activity of crude enzyme in (Capsicum annuum) was 90.51 U/mg (Table 2), while on purification specific activity of 234 U/mg was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Chili peppers are rich in many minerals, vitamins, and amino acids essential for human health and growth. Peppers contain a wide array of phytochemicals such as vitamins, phenolics, and flavonoids that have anti-oxidants, antimicrobial and anti-degenerative properties ( Jagtap et al, 2012 , Omolo et al, 2014 , Fattori et al, 2016 , Ganguly et al, 2017 , Saleh et al, 2018 ). The cultivation of Chilli is severely affected by many diseases caused by multiple pathogens including viruses, fungus, bacteria and nematodes.…”
Section: Introductionmentioning
confidence: 99%